2014
DOI: 10.1186/1746-1596-9-7
|View full text |Cite
|
Sign up to set email alerts
|

Cruciferous vegetables consumption and the risk of ovarian cancer: a meta-analysis of observational studies

Abstract: BackgroundTo quantify the effect of cruciferous vegetable consumption on the incidence of ovarian cancer by meta-analyzing the existing observational studies and provides quantitative and high-level evidence.MethodsA detailed literature search of Medline and EMBASE for all relevant papers published. A meta-analysis was conducted for the association between cruciferous vegetable consumption and risk of ovarian cancer.ResultsA total of 4,306 cases in 375,562 controls in 11 independent studies were identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…Our studies have demonstrated that purified sulforaphane is able to overcome the pronounced therapy resistance of PDA in vitro and in vivo [7,8], and similar results have been obtained in experimental models of prostate and breast cancer [8][9][10][11]. Epidemiological studies have suggested that the frequent intake of cruciferous vegetables might be inversely associated with the risk of developing pancreatic cancer [12][13][14][15][16], as well as cancer of the breast, kidney, bladder and prostate [17][18][19][20][21][22]. A Canadian study observed a significantly decreased risk of extra-prostatic manifestations of stage III and IV prostate cancer when men frequently consumed broccoli and cauliflower [17].…”
Section: Introductionsupporting
confidence: 80%
“…Our studies have demonstrated that purified sulforaphane is able to overcome the pronounced therapy resistance of PDA in vitro and in vivo [7,8], and similar results have been obtained in experimental models of prostate and breast cancer [8][9][10][11]. Epidemiological studies have suggested that the frequent intake of cruciferous vegetables might be inversely associated with the risk of developing pancreatic cancer [12][13][14][15][16], as well as cancer of the breast, kidney, bladder and prostate [17][18][19][20][21][22]. A Canadian study observed a significantly decreased risk of extra-prostatic manifestations of stage III and IV prostate cancer when men frequently consumed broccoli and cauliflower [17].…”
Section: Introductionsupporting
confidence: 80%
“…Tests on animals and in vitro tests drew attention to the degradation products of glucosinolates which suppress the division of cancer cells, and accelerate the controlled death of the cell with damaged DNA. Furthermore, the protective effect of the enzyme degradation products of glucosinolates is associated with the induction of detoxifying enzymes in the tissues of the gastrointestinal tract, particularly of glutathione transferase, levelling the active form of carcinogenic compounds [21,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Diet may be modifying the risk of ovarian cancer through effect on endogenous hormones, antioxidant activity or other anticarcinogenic mechanisms. There is however a unanimous finding of reduced incidence of ovarian cancer with higher intake of vegetables especially for epithelial ovarian cancer [106][107][108][109][110][111]. The average finding is a reduction of risk by about more than 50%.…”
Section: Diet and Ovarian Cancermentioning
confidence: 99%